Constituição da identidade docente de bacharéis em engenharia: narrativas do habitar a docência na universidade - Gagliato, Jéferson Felipe (2023)
This study addresses the Constitution of the teaching identity of Bachelor's degree holders in Engineering: narratives of inhabiting teaching at the University. The main objective of the study was to understand the process of constitution of the identity of Bachelor's degree teachers in Engineering at the State University of Feira de Santana-UEFS, Bahia. The methodology of this research is qualitative in nature and is grounded in the (auto)biographical approach. As a data collection device, narrative interviews were used, which were recorded, transcribed, and analyzed in light of the comprehensive and interpretive paradigm of Ricouer (2012) and Souza (2014). The research involved the collaboration of four university professors from engineering courses (Civil, Food, and Computing) at UEFS. In the theoretical field, the research is based on theoretical contributions that address concepts such as teaching identity, experience, teaching profession, ongoing training, among others. The constitution of the teaching identity of Bachelor's degree holders in Engineering: narratives of inhabiting teaching at the University requires a deep understanding and evaluation of the knowledge, practices, and experiences that permeate their activities. The results allow us to conclude that professional identities are constituted by the trajectory of professional performance. The narratives revealed processes of subjectivization that each professor produces when narrating about their own role in university teaching, intersected by family experiences. The study also allowed us to conclude that identities are flexible and are formed based on the experiences that each teacher builds in their professional journey.